2006
DOI: 10.1515/bc.2006.121
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calcineurin by infusion of CsA causes hyperphosphorylation of tau and is accompanied by abnormal behavior in mice

Abstract: Calcineurin is a Ca2+/calmodulin-dependent phosphatase that dephosphorylates numerous substrates in different neuronal compartments. Genetic and pharmacological studies have provided insight into its involvement in the brain. Cyclosporin A (CsA) is used as a specific calcineurin inhibitor in many pharmacological experiments. However, the calcineurin activity of CsA-treated brain has not been reported. To examine the relationship between calcineurin activity and brain function, we injected CsA into the left lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…In non-transgenic mice, reduction of calcineurin protein and activity by anti-sense oligonucleotides also results in increased phosphorylation at Thr181 and Thr231 in tau (Garver, et al, 1999). Inhibition of calcineurin with CsA or FK506 treatment in Tg2576 mice results in the reduction of calcineurin activity and enhanced tau phosphorylation at Ser262, Ser198, Ser199, Ser202, Ser396, and Ser404 (Luo, et al, 2008, Yu, et al, 2006a). In our cell model, upon treatment of cells with calcineurin inhibitors, we detected increases in intracellular ptau181 and extracellular total and ptau181.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-transgenic mice, reduction of calcineurin protein and activity by anti-sense oligonucleotides also results in increased phosphorylation at Thr181 and Thr231 in tau (Garver, et al, 1999). Inhibition of calcineurin with CsA or FK506 treatment in Tg2576 mice results in the reduction of calcineurin activity and enhanced tau phosphorylation at Ser262, Ser198, Ser199, Ser202, Ser396, and Ser404 (Luo, et al, 2008, Yu, et al, 2006a). In our cell model, upon treatment of cells with calcineurin inhibitors, we detected increases in intracellular ptau181 and extracellular total and ptau181.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin (PP3, previously PP2B) is a heterodimeric calcium/calmodulin-dependent phosphatase composed of a 60 kDa catalytic subunit (PPP3CA) and a 19 kDa calcium binding regulatory subunit (PPP3R1) (reviewed in (Rusnak and Mertz, 2000)). The 60 kDa catalytic subunit possesses a catalytic domain, regulatory subunit binding domain, calmodulin binding domain, and autoinhibitory domain at the C-terminus (Yu, et al, 2006a). Calcineurin is abundantly expressed in the cytosol of neuronal cells in the brain (Dawson, et al, 1994, Goto, et al, 1986, Polli, et al, 1991) where it directly dephosphorylates tau at Thr181, Thr231, and Ser396 (Garver, et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Calcineurin which regulates the dephosphorylation of TRESK, is also proved to negatively affect the memory by modulating the neuron plasticity, though it is critical in the form of the learning and memory in normal condition [29,30,39] . The activator of calcineurin has proved to improve the impaired memory in experimental animal [36,39] .…”
Section: Tresk and Volatile Anestheticsmentioning
confidence: 99%
“…Calcineurin which regulates the dephosphorylation of TRESK, is also proved to negatively affect the memory by modulating the neuron plasticity, though it is critical in the form of the learning and memory in normal condition [29,30,39] . The activator of calcineurin has proved to improve the impaired memory in experimental animal [36,39] . Though many receptors and channels are involved in the mechanism of volatile general anesthesia, the special activation pathway in TRESK affected by calcineurin and the relationship between calcineurin and memory make us to predict that TRESK may be relevant to the memory impair induced by volatile Fig.…”
Section: Tresk and Volatile Anestheticsmentioning
confidence: 99%
“…In our previous study, we showed that inhibition of CN by cyclosporin A (CsA) can induce hyperphosphorylation of tau at multiple sites in mouse brain (Yu et al 2006a). CsA, a specific inhibitor of CN, inhibits CN activity by forming complexes with cytoplasmic immunophilins, cyclophilins (Liu et al 1991;Fruman et al 1992).…”
Section: Introductionmentioning
confidence: 99%